MACROMEDIA FLASH-BASED LEARNING MEDIA AND LEARNING MOTIVATION ON MATHEMATICS LEARNING OUTCOMES - Lisma Dian Kartika Sari; Maswar Maswar; Ida Fitriana Ambarsari; Nur Hasanah (STKIP PGRI Situbondo, 2023)
The development of technology, especially Information and Communication Technology (ICT) has influenced all aspects of life including education. Learning mathematics requires a tool (media) to explain mathematical material that is abstract in nature and fosters student learning motivation. Macromedia flash is a vector-based animation program and is used to create animated objects and text. This study aims to determine the effect of macromedia flash-based learning media and learning motivation on learning outcomes of class X IPA students at SMAN 1 Asembagus. The population is 180 students of class X IPA which consists of 5 classes, while the sample taken is 124 students of class X IPA. Data collection techniques used questionnaire and documentation techniques, while data analysis in this study used multiple regression analysis. The results of this study indicate that simultaneously learning media based on macromedia flash and learning motivation towards mathematics learning outcomes is 6,2%. While partially macromedia flash based learning media has an effect of 0,0027% and learning motivation has an effect of 0,059%. Based on the results of the study, it can be concluded that there is the influence of macromedia flash based learning media and learning motivation on the mathematics learning outcomes of class X IPA at SMAN 1 Asembagus both simultaneously and partially.